The Economics of Auto-Delivery: A Qualitative Exploration of Inventory Management and Profitability in Subscription Services - Permana, Ngadi; Amelia, Yessica; Rizal, Muhammad (International Journal of Business, Marketing, Economics & Leadership (IJBMEL), 2024)
This qualitative literature review examines "The Economics of Auto-Delivery: A Qualitative Exploration of Inventory Management and Profitability in Subscription Services." Auto-delivery systems have gained traction in various industries, offering consumers convenience and suppliers a steady revenue stream. This study synthesizes existing literature to uncover the interplay between inventory management, profitability, and consumer behavior within auto-delivery frameworks. Key findings highlight the importance of advanced inventory strategies, dynamic pricing models, and the role of technology in enhancing operational efficiency. Additionally, the review discusses the implications of consumer behavior on subscription retention and the challenges suppliers face in minimizing churn. The insights derived from this review indicate that effective channel coordination and strategic investment in technology are essential for maximizing the profitability of auto-delivery services. However, the study acknowledges limitations such as the predominance of research in Western markets and the lack of empirical data to support theoretical insights. This review provides a comprehensive understanding of the economics surrounding auto-delivery systems, serving as a foundation for future research in this rapidly evolving domain.